Research on Full Life Cycle Management of Cold Chain Logistics Park based on Internet of Things and Digital Twin - Jia, Yongqiang (International Journal of Social Sciences and Public Administration, 2025)
Cold chain logistics park, as a key infrastructure to ensure the safety of food and medicine, faces the challenges of low automation, high energy consumption, and dispersed management. This paper constructs a framework for the whole life cycle management of cold chain logistics parks based on the Internet of Things (IoT) and digital twins, describes the technical paths of physical entity modelling, data acquisition and processing, and virtual-reality mapping and interaction, and systematically explores the application mechanism of this technology in the stages of planning, designing, construction and implementation as well as operation and maintenance. The study shows that the integration of IoT and digital twin technology can effectively improve the operational efficiency, quality management level and resource utilisation of cold chain logistics parks, providing a feasible path for the digital transformation of the industry.